Stimulasi Bahasa Anak Usia Dini Melalui Metode Bercerita - Meida Afina Putri Afina (UIN Raden Mas Said Surakarta, 2020)
Language development is important to early childhood in their communication and interaction to others. Story is the most important stimulus to enhance early childhood speaking actively. Instead of gluing early childhood to digital world, parent and teacher must be concern to lift story method issues for learning process of early childhood. This study employs qualitative method by gathering data from scientific books and journals as a way to elaborate story method for enhancing early childhood communication and interaction. The result shows that story method is quite effective to triger early childhood for communicating and interacting to others. Through listening to children's stories, they will reveal the contents of the story again. That way, children can train their speech to convey ideas and verbal forms. In addition, children will also get lessons or advice through stories by educating smart people. So as to provide satisfaction with the need for imagination and fantasy. By the research design, it suggests to teacher of early childhood emphasizing story method as learning process.